Saturation Model for Plastic-Iron Composites with Low Iron Concentration - Dreishing, Florian; Kreischer, Christian (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
This paper deals with the experimental magnetic characterization of composites made of a plastic base material and iron-powder. The iron concentration is kept very low to obtain a low permea-ble but mechanically soft material for the construction of a bend-able linear motor. From the experimental characterization a saturation model is derived that can be used for a Finite Element Analysis to study, if the force-to-weight-ratio of the bendable linear motor can be increased using the plastic-iron composite.